1984
DOI: 10.1007/bf00398722
|View full text |Cite
|
Sign up to set email alerts
|

The crystalline polymorphism of mannan in plant cell walls and after recrystallisation

Abstract: Mannan-rich plant cell walls were mechanically disintegrated and chemically extracted in order to ascertain their morphology and structure by electron microscopy and electron diffraction. For Acetabularia crenulata and Codium fragile, the cell-wall fragments were found to consist of alkali-resistant fibrillar mannan II encrusted with alkali-soluble granular mannan I. In the case of ivory nuts (Phytelephas macrocarpa) there is, in addition, a microfibrillar cellulose component which was also identified. The man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 20 publications
2
65
1
Order By: Relevance
“…Furthermore, mannan is also found in some red algae, such as Porphyra umbilicalis (Jones, 1950). In some of these algae, mannan is the main structural polymer and displays microfibrillar morphology (Chanzy, Grosrenaud, Vuong, & Mackie, 1984).…”
Section: Mannansmentioning
confidence: 99%
“…Furthermore, mannan is also found in some red algae, such as Porphyra umbilicalis (Jones, 1950). In some of these algae, mannan is the main structural polymer and displays microfibrillar morphology (Chanzy, Grosrenaud, Vuong, & Mackie, 1984).…”
Section: Mannansmentioning
confidence: 99%
“…It was shown that with mannan and glucomannan polymers, the mannan I structure was obtained more easily with low molecular weight material, whereas mannan II corresponded to higher molecular weight (4,8). A close resemblance exists thus between the crystallization of cellulose IV^ and mannan I as with both polymers, the crystallization phenomena appear to be directed by related parameters.…”
Section: Discussionmentioning
confidence: 83%
“…This is in particular described in the case of mannan and glucomannan polymers (4,8) where crystals of mannan I are usually obtained with low degree of polymerization (DP) material, whereas only mannan II is found when higher DP are recrystallized.…”
mentioning
confidence: 95%
“…Adsorption experiments were performed in 50 mM sodium acetate buffer, pH 4.0, using 0.1% cellulose, xylan, mannan, arabinan, or chitin. These insoluble carbohydrates were prepared as described elsewhere (3,9,44,49,52). The protein concentrations in the additive solutions were calculated from the absorbance at 420 nm (ε 420 ϭ 130 mM remove the precipitates completely, and the protein concentrations in the supernatants were determined again.…”
Section: Methodsmentioning
confidence: 99%